Feasibility of training service providers on the AMBIANCE‐Brief measure for use in community settings. Issue 3 (10th December 2020) - Madigan, Sheri; Eirich, Rachel; Racine, Nicole; Borland‐Kerr, Catherine; Cooke, Jessica E.; Devereux, Chloe; Plamondon, André R.; Tarabulsy, George M.; Cyr, Chantal; Haltigan, John D.; Bohr, Yvonne; Bronfman, Elisa; et al.
ABSTRACT: The Atypical Maternal Behavior Instrument for Assessment and Classification—Brief (AMBIANCE‐Brief) was developed to provide a clinically useful and psychometrically sound assessment of disrupted parenting behavior for community practitioners. With prior evidence of this tool's reliability and validity in laboratory settings, this study aimed to determine whether providers from family service agencies could become reliable in the use of the level of disrupted communication following a brief training. Providers ( N  = 46) from three agency sites participated in a 2‐day AMBIANCE‐Brief training and, at the end of the training, coded eight videotaped mother–child interactions. Novice participant coding was compared to expert consensus ratings using intraclass correlations. On average, participants' interrater agreement was good (ICCmean  = .84, SD  = 0.10), with 89% meeting the reliability standards of ICC ≥ .70. In response to queries, 100% of participants indicated that they would recommend the AMBIANCE‐Brief training to their colleagues, 85% reported that the AMBIANCE‐Brief measure would be useful or very useful for their clinical practice, and 56% of participant clinicians believed that parents would find the measure acceptable or very acceptable for integration into intervention or support planning. Altogether, these findings speak to the feasibility of using the AMBIANCE‐Brief in community settings. Future studies are needed in diverse clinical and community contexts to evaluate whether use of this assessment tool can inform more targeted interventions tailored to the specific needs of families. RESUMEN: El Instrumento Abreviado para Evaluación y Clasificación de la Conducta Materna Atípica (AMBIANCE‐Abreviado; Madigan, Bronfman, Haltigan y Lyons‐Ruth, 2018) se desarrolló para ofrecer a quienes practican en la comunidad una evaluación clínicamente útil y sicométricamente acertada de la conducta de crianza trastornada. Con la anterior evidencia de la confiabilidad y validez de esta herramienta en el marco de los laboratorios (Cooke, Eirich, Racine, Lyons‐Ruth y Madigan, 2020), este estudio se propuso determinar si se podría confiar en quienes proveen el servicio como parte de las agencias de servicio a las familias después de un breve entrenamiento. Los proveedores (N = 46) de tres lugares de agencias participaron en un entrenamiento de dos días sobre AMBAIANCE‐Abreviado y, al final del entrenamiento, codificaron ocho interacciones madre‐niño grabadas en video. Se comparó la forma de codificar de los novatos con el puntaje consenso de los expertos usando correlaciones dentro de clases. El acuerdo entre los evaluadores fue bueno (ICC media = .84, SD = 0.10), con un 89% de los participantes que lograron el estándar de confiabilidad de ICC > .70. En respuesta a preguntas, el 100% de los participantes indicó que ellos recomendarían el entrenamiento de AMBIANCE‐Abreviado a sus colegas, 85% reportó que la medida AMBIANCE‐Abreviado sería útil o muy útil en su práctica clínica, y 56% creían que los progenitores encontrarían la medida aceptable o muy aceptable para ser integrada en la intervención o el planeamiento de apoyo. En conjunto, estos resultados hablan de la factibilidad de usar AMBIANCE‐Abreviado en el marco comunitario. RÉSUMÉ: L'Instrument d'Evaluation et de Classification‐Brève du Comportement Maternel Atypique (AMBIANCE‐Bref; Madigan, Bronfman, Haltigan, & Lyons‐Ruth, 2018) a été développé afin d'offrir une évaluation du comportement de parentage perturbé, cliniquement utile et saine du point de vue psychométrique, pour les acteurs communautaires. Avec des preuves préalables de la fiabilité et de la validité de cet outil en laboratoire (Cooke, Eirich, Racine, Lyons‐Ruth, & Madigan, 2020), cette étude s'est donné pour but de déterminer si les prestataires des agences de service à la famille pouvaient devenir fiables pour son utilisation après une formation courte. Des prestataires (N = 46) de trois sites d'agence ont participé à une formation AMBIANCE‐Bref de deux jours et à la fin de la formation ont codé huit interactions mère‐enfant filmées. Le codage du participant débutant a été comparé aux évaluations par consensus d'expertes en utilisant des corrélations intraclasses. Le coefficient d'objectivité était bon (moyenne des coefficient de corrélation intraclasse [ICC] = 84, SD = 0, 10), avec 89% des participants remplissant les standards de fiabilité d'ICC ICC ³, 70. En répondant aux questions, 100% des participants ont indiqué qu'ils ou elles recommanderaient la formation AMBIANCE‐bref à leurs collègues, 85% ont indiqué que la mesure AMBIANCE‐bref serait utile ou très utile pour leur pratique clinique, et 56% ont déclaré qu'ils ou elles croyaient que les parents trouveraient cette mesure acceptable ou très acceptable pour une intégration à une intervention ou le plan de soutien. Au total, ces résultats parlent de la viabilité de l'utilisation de l'AMBIANCE‐bref dans des contextes communautaires. ZUSAMMENFASSUNG: Das AMBIANCE‐Brief: Schulungen zur Verwendung des Instruments für Praktizierende in Community‐Settings Die Kurzform des Instruments zur Bewertung und Klassifikation von atypischem mütterlichem Verhalten (Atypical Maternal Behavior Instrument for Assessment and Classification‐Brief; AMBIANCE‐Brief; Madigan, Bronfman, Haltigan & Lyons‐Ruth, 2018) wurde entwickelt, damit Praktizierende in Community‐Settings auf ein klinisch brauchbares und psychometrisch fundiertes Beurteilungsmaß für gestörtes Elternverhalten zurückgreifen können. Gestützt durch im Laborsetting bereits erbrachte Reliabilitäts‐ und Validitätsnachweise (Cooke, Eirich, Racine, Lyons‐Ruth & Madigan, 2020), sollte in dieser Studie untersucht werden, ob Praktizierende durch eine kurze Schulung zu einer reliablen Verwendung des Instruments befähigt werden. Mitarbeitende (N = 46) von drei Leistungsträgern nahmen an einer zweitägigen AMBIANCE‐Brief‐Schulung teil und kodierten am Ende der Schulung 8 auf Video aufgezeichnete Mutter‐Kind‐Interaktionen. Die Kodierungen der Teilnehmenden wurden mithilfe von Intraklassen‐Korrelationen mit Konsens‐Ratings von Expert_innen verglichen. Die Interrater‐Übereinstimmung war gut (ICCmean = .84, SD = 0.10), wobei 89% der Teilnehmenden den Reliabilitätsstandard von ICC > .70 erfüllten. 100% der Teilnehmenden gaben an, dass sie ihren Kolleg_innen die AMBIANCE‐Brief Schulung empfehlen würden, 85% schätzten das AMBIANCE‐Brief Instrument als nützlich oder sehr nützlich für ihre klinische Praxis ein und 56% glaubten, dass das Instrument bei Eltern bzgl. einer Integration in die Interventions‐ oder Unterstützungsplanung auf Akzeptanz stoßen würde. Insgesamt sprechen diese Ergebnisse für die Durchführbarkeit des AMBIANCE‐Briefs in Community‐Settings. 抄録: 地域社会でのトレーニングされたサービス・プロバイダーの簡易‐AMBIANCE評価使用についての実現可能性 非定型母性行動の評価と分類のためのツールの簡易版(AMBIANCE‐Brief; Madigan, Bronfman, Haltigan, & Lyons‐Ruth, 2018) は、地域の臨床家にとって、混乱した子育て行動に対して臨床的に役立ち心理測定的に健全な評価を提供できるように開発された。実験室でのこのツールの信頼性と有効性の事前証拠(Cooke, Eirich, Racine, Lyons‐Ruth, & Madigan, 2020)と共に、本研究では、家族サービス機関のプロバイダーが短期の訓練後にその使い方について信頼性のあるものになっているかどうかについて究明することを目的とした。3つの機関からのプロバイダー(N = 46人)が、2日間の簡易‐AMBIANCE訓練に参加し、訓練の終了時に8つの録画された母子相互作用をコード化した。初心者でもある参加者のコーディングは、級内相関を使って専門家コンセンサス評価と比較した。評価者間合意は良く(ICCmean = .84, SD = 0.10)、参加者の89％がICC .70の信頼性基準を満たしていた。質問に対しての答えでは、参加者の100％が簡易‐AMBIANCE訓練を同僚に勧めると述べ、85％が簡易‐AMBIANCE評価が自分たちの臨床において役に立つあるいは大いに役に立つと報告した。また56％が、親が介入やサポート計画に対し、その評価を統合することに関して受け止めるあるいは大いに受け止めるであろうと信じていた。つまりこれらの結果は、地域社会における簡易‐AMBIANCE評価使用についての実現可能性を明らかにした。 摘要: 开发"简便类型的非典型母亲行为评定分类系统" (AMBIANCE‐Brief; Madigan, Bronfman, Haltigan, & Lyons‐Ruth, 2018) 的目的是为社区从业者提供对养育行为中断在临床上有用的、心理测量上合理的评估。借助该工具在实验室环境中的可靠性和有效性的先前证据 (Cooke, Eirich, Racine, Lyons‐Ruth, & Madigan, 2020), 本研究旨在确定来自家庭服务机构的从业者在经过短暂培训后是否能够可靠地使用该工具。来自三个机构地点的从业者 (N = 46) 参加了为期两天的AMBIANCE‐Brief培训, 并在培训结束时, 编码了八段录制的母子互动视频。利用组内相关性将新手参与者编码与专家共识评级进行比较。组间一致性很好 (ICCmean = .84, SD = 0.10), 其中89％的参与者符合ICC .70的可靠性标准。在回答询问时, 100%的参与者表示他们会向同事推荐AMBIANCE‐brief培训, 85%的参与者报告AMBIANCE‐brief测量对他们的临床实践是有用或非常有用的, 56%的参与者认为父母可以接受或非常接受该测量纳入干预或援助计划中。总之, 这些发现说明了在社区医疗机构中使用AMBIANCE‐Brief的可行性。 ملخص: جدوى تدريب مقدمي الخدمات على إجراء مقياس (Brief‐AMBIANCE) للاستخدام في السياق المجتمعي مقياس السلوك الأمومي الغير نمطي المختصر (brief‐Ambiance) تم تطويره من خلال دراسات ماديجان، برونفمان، هالتيغان، وليونس روث، 2018 لتوفير تقييم مفيد وسليم إكلينيكياً لسلوك الأبوة والأمومة المضطرب وذلك ليستخدمه الممارسون في السياق المجتمعي. ومع الأدلة المسبقة على موثوقية وصلاحية هذه الأداة في السياقات المعملية(كوك، آيريش، راسين، ليونز روث، وماديجان، 2020)، تهدف هذه الدراسة إلى تحديد ما إذا كان مقدمو الخدمات من هيئات الخدمات الأسرية يمكن أن يصبحوا موثوقين في استخدامها بعد تدريب قصير. شارك مقدمو الخدمات(N = 46) من ثلاثة مواقع تابعة لهيئات خدمات الأسرة في تدريب على استخدام (Brief‐AMBIANCE) لمدة يومين، وفي نهاية التدريب، قاموا بتحليل ثمانية تفاعلات مسجلة بالفيديو بين الأم والطفل. وتم بعد ذلك مقارنة تقييم المشاركين المبتدئين مع تقييمات إجماع الخبراء باستخدام الارتباطات داخل المجموعات. وكان نتيجة الاتفاق جيدة (ICC = .84 و SD = 0.10) حيث حقق 89 % من المشاركين معايير الموثوقية (ICC = 0.70 أو:أكبر). ورداً على الاستفسارات، أشار 100 في المائة من المشاركين إلى أنهم سيوصون بـ "التدريب المختصر لـ"AMBIANCE" لزملائهم، وأفاد 85% منهم بأن المقياس الموجز لـAMBIANCE سيكون مفيداً أو مفيداً جداً لممارستهم الإكلينيكية، ويعتقد 56% أن الآباء سيجدون أن المقياس مقبول أو مقبول جداً للاستخدام في التدخل التجريبي أو دعم التخطيط. وتتحدث هذه النتائج بشكل إجمالي عن جدوى استخدام المقياس المختصر AMBIANCE في السياقات المجتمعية.